ECOLOGICAL STUDY OF LITERATURE IN GEGURITAN KENDENG KAYA AMBENG - Gunawan, Eko (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to examine the Kendeng Kaya Ambeng geguritan text using literary ecology. This research uses qualitative descriptive research. The data were collected using reading and note-taking techniques. This research utilises literature study techniques to strengthen the primary data collected. After that, the collected data are processed through a series of stages, including 1) data selection, 2) data interpretation, and 3) concluding the research results. Through a literary ecology approach, "Kendeng Kaya Ambeng" can be understood as a sharp criticism of environmental exploitation that harms local communities, especially farmers. The text highlights the conflict between development (which often only benefits certain parties) and the need to maintain ecological balance and the sustainability of human life. This genre's representation of environmental damage reminds us of the importance of harmony between humans and nature to prevent a bigger crisis.